Fiber optic control system for geotechnical parameters of mine - A. D. Mekhtiyev; A. I. Soldatov; Ye. G. Neshina; A. D. Alkina (Омский научный вестник)
In the article a fiber-optic method for monitoring rock pressure is considered, as well as the magnitude of the displacement of the layers of the stope hanging wall is measured. The authors analyze the applied rock pressure testing methods. The reasons for the need to create a safe system are given, the main requirement of which is the condition of compliance with all safety requirements during mining operations. The developed quasi-distributed fiber-optic system is capable of measuring with high accuracy changes in rock pressure and displacement of roof rocks in an explosive environment, also does not require expensive equipment associated with the use of a range of analyzers and reflectometers. A scheme has been proposed to simplify the testing process. The results of dependences of additional optical losses on the applied force are obtained.